TDRI + LRDC = ODNRI - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
TDRI + LRDC = ODNRIIl faudra désormais apprendre un nouveau sigle, l'ODNRI. Ce nouveau venu dans le monde du développement est né de la fusion du TDRI (Tropical Development and Research Institute) et du LRDC (Land Resources Development Centre),...